Inventarios de fauna y flora en relictos de bosque en el enclave seco del río Amaime, Valle del Cauca, Colombia (2014)
The dry enclave of Amaime River is one of the few places that remain as Tropical Dry Forest in the Valle del Cauca department, which is considered one of the most threatened ecosystems in the Neotropics. The site has been heavily transformed and threatened by anthropic means like continued burning for the suitability of land for agriculture and livestock, small short rotation crops among others. The aim of the study was to develop detailed inventories of avifauna, herpetofauna, mammalian fauna, and flora in relict sub-xerophytic forests of the enclave, therefore revealing the biodiversity of these remnants, their conservation status and potential threats in order to propose recommendations for conservation. Four sampling areas were selected with cover vegetation as thorny scrub vegetation, riparian forests and forest fragments. For registration and data collection mist nets, transects, direct observations and Sherman traps were used, additionally informal interviews with the community were performed. Despite the reduction of vegetation cover in the dry enclave of Amaime River, the forest fragments serve as shelter and feeding site for both transient species and typical dry and very dry forest wildlife.